Government Supervision in The Management of School Operational Assistance Fund in Singkawang City - Agus Satriawan; Dede Sri Kartini; Antik Bintari (Journal of Law, Politic and Humanities, 2025)
This study aims to evaluate the effectiveness of monitoring the management of School Operational Assistance (Bantuan Operasional Sekolah/BOS Funds in Indonesian) funds in Singkawang City. The main focus of this research is to measure the success of supervision based on three indicators proposed by Arifin Abdul Rachman: increasing discipline and achieving task implementation targets, reducing abuse of authority, and minimizing errors in task implementation. This study employs a qualitative approach with a case study method, involving in-depth interviews with various informants, including school principals, treasurers, auditors, and the community. The findings reveal that the monitoring of BOS fund management in Singkawang City has been relatively effective, with several significant insights. The first indicator indicates that most schools have prepared their School Activity and Budget Plan in compliance with regulations, although challenges remain in budget implementation and reporting delays. For the second indicator, no significant abuse of authority was identified, but there are still weaknesses in technical understanding, particularly regarding taxation. The third indicator highlights that administrative errors, such as asset recording and tax reporting, remain key challenges. Initiatives like the BOS Fund Clinic organized by the Inspectorate are seen as positive steps to address these issues. This study recommends enhancing technical training for school principals and treasurers, strengthening monitoring capacity through system digitization, and increasing community participation in supervision to foster better transparency and accountability. These measures are expected to optimize the management of BOS funds in supporting improvements in education quality.